Oral Anticoagulation Persistence in Atrial Fibrillation - Paquette, Miney (My University, 2020)
Long-term persistence with oral anticoagulants (OAC) in atrial fibrillation (AF) is associated with improved outcomes. However, 1-year discontinuation of vitamin K antagonists (VKA) is as high as 50%. Persistence to non-VKA oral anticoagulants (NOAC) show some signal of improvement but the estimates are variable. This thesis includes a prospective evaluation of newly diagnosed AF patients in 44 countries using physician reported start and stop dates of anticoagulation. One-year persistence to dabigatran was 75.6% and 69.2% at 2 years. Approximately half of discontinuers switched to another OAC, increasing estimates of general overall 2-year OAC persistence to 84.1%. Probability of discontinuation was highest in the first 6 month period (83.7%, 95% confidence interval [CI] 82.7-84.8%) and lower in successive periods. Patients persistent with dabigatran at 1 year had >90% probability of remaining persistent at 2 years. Patients with symptomatic AF, and prior bleeding had higher discontinuation, those with prior stroke, lower discontinuation. Standardized stroke incidence rates post-discontinuation were (95% CI) 1.76 (0.89 to 2.76) in non-switchers, and 1.02 (0.43 to 1.76) in those who switched, consistent with the expected benefit of remaining on treatment. Supplemental patient education may be one mechanism to improve persistence to treatment and improve patient outcomes. A systematic review of the impact of education on outcomes in 9 randomized clinical trials showed low to very low certainty of evidence for benefit of education over usual care. Sufficiently powered trials or different approaches are required to further assess the impact of education on patient outcomes. Finally, important considerations for interpreting available research in OAC persistence, including differences in study methodology, setting, and timing are examined, and patient factors associated with higher or lower persistence reported. A framework for assessing persistence studies is presented to assist researchers and clinicians in evaluating current research and to support planning of future studies.
Evaluating Oral Anticoagulation Persistence in Patients with Atrial Fibrillation
PhD Thesis
Keywords: Persistence; Anticoagulation